Bremsstrahlung of polarized positrons scattered off atoms - Yerokhin, Vladimir; Tashenov, Stanislav (Physica scripta, 2013)
The leading-order positron-atom bremsstrahlung is investigated within the rigorous relativistic approach based on the partial-wave representation of the Dirac wave functions in the external atomic field. Approximating the atomic target by an effective local potential, we calculate the Stokes parameters of the emitted photon for different polarizations of the initial positron. The results for positron-atom bremsstrahlung are compared with analogous data for the electron-atom bremsstrahlung.
Gesehen am 26.07.2021